PENGARUH PENERAPAN SAMSAT DIGITAL NASIONAL DAN SAMSAT KERTI TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN BULELENG - Rahayuni, Ni Putu Vira Sinta; Darmawan, Nyoman Ari Surya; Putra, I Putu Yunartha Pradnyana (Universitas Pendidikan Ganesha, 2025)
This research was conducted with the aim to determine the influence of the National Digital Samsat application (SIGNAL) and the Samsat Kerti service on motor vehicle taxpayers’ compliance in Buleleng Regency. This research is classified as a quantitative study, in which primary data were used. The primary data were collected by distributing questionnaires online via Google Form. The population of this research consists of 524,799 motor vehicle taxpayers registered at the Joint Samsat Office of Buleleng. The sampling technique used is purposive sampling, and the total sample determined was 100 respondents, who are motor vehicle taxpayers domiciled in Buleleng Regency and have used both the SIGNAL application and Samsat Kerti service. The techniques used to analyze the data include Descriptive Statistical Analysis, data quality testing, classical assumption tests, multiple linear regression analysis, t-tests, and the coefficient of determination (R²), all processed using SPSS version 26.0 for Windows. This research found that both the SIGNAL application (X1) and Samsat Kerti service (X2) have a positive and significant influence on motor vehicle taxpayer compliance (Y) in Buleleng Regency.